2017
DOI: 10.1002/joc.5170
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and the recent warming of the Indian Ocean

Abstract: ABSTRACT:The recent Indian Ocean (IO) warming and its relation with the El Niño Southern Oscillation (ENSO) is investigated using available ocean and atmospheric reanalyses. By comparing the events before and after 1976 (identified as a threshold separating earlier and recent decades with respect to global warming trends), our results indicate that the IO had experienced a distinct change in the warming pattern. After 1976, during the boreal summer season the cold anomalies in the IO were replaced by warm anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Weak (strong) wind typically occurs during El Niño (La Niña) [64,65]. However, after the early 1980s, there was a weakening and shift that were included behind the surface wind to the SST [58,66], which means that this shift took place over 30 years ago and still continues, which is consistent with our results. Nakamura et al (2009) [67] suggested that a warming of the Western IO has driven the observed shift by acting as a barrier for ENSO influencing the IO circulation, including the GA and RS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Weak (strong) wind typically occurs during El Niño (La Niña) [64,65]. However, after the early 1980s, there was a weakening and shift that were included behind the surface wind to the SST [58,66], which means that this shift took place over 30 years ago and still continues, which is consistent with our results. Nakamura et al (2009) [67] suggested that a warming of the Western IO has driven the observed shift by acting as a barrier for ENSO influencing the IO circulation, including the GA and RS.…”
Section: Discussionsupporting
confidence: 91%
“…This situation forces the normal surface wind in the IO either to be weak westerly or to completely change direction to easterly. Previous studies reported vividly that the dominant mode of surface wind and SST in the IO is closely related to ENSO [49,51,[56][57][58].…”
Section: Discussionmentioning
confidence: 96%
“…Then what could have caused the strengthening of surface westerlies? We now turn attention to the tropical Indian Ocean (TIO) whose temperature has increased by about 1°C since the mid-1950s [17][18][19][20][21][22][23][24][25][26][27] , at a faster rate than that of the other two tropical oceans ( Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the longterm persistence of MHWs in the western Indian Ocean region is associated with the background SST warming primarily identified with the Indian Ocean basin-wide warming (IOB) and also the El Niño, IOD, and NAO Roxy et al (2014). andAbish et al (2018) show that the western Indian Ocean is warming at a rapid pace since the 1950s, largely in response to anthropogenic warming but manifested through an asymmetry in the ENSO impact-whereby El Niño events cause anomalous warming in the western Indian Ocean and La Niña events fail to cool the region. They also found that the ENSO events are more intense in the recent decades and this result in a positive SST skewness Han et al (2010).…”
mentioning
confidence: 99%